Pengaruh Struktur Modal Dan Likuiditas Terhadap Profitabilitas Pada Perusahaan Pertambangan Yang Terdaftar Di Bursa Efek Indonesia Tahun 2020-2024 - Aliah, Ida Istania; Rastryana, Ulta; Irawan, Rini Larasati (CV Warnak Johanna Nusantara, 2025)
This study aims to analyze the effect of capital structure and liquidity on profitability in mining sub-sector companies listed on the Indonesia Stock Exchange during the 2020– 2024 period. The background of this research is based on the importance of financial management in mining companies, which require large capital and face high risks due to fluctuations in global commodity prices. The variables used in this study are capital structure measured by Debt to Equity Ratio (DER), liquidity measured by Current Ratio (CR), and profitability proxied by Return on Assets (ROA). This research applies a quantitative approach with a purposive sampling technique, resulting in 21 companies as the sample. Data were analyzed using multiple linear regression with SPSS version 26. The results show that, partially, capital structure has a negative and significant effect on profitability, while liquidity has a positive and significant effect on profitability. Simultaneously, capital structure and liquidity significantly affect profitability with a significance value of 0.000 < 0.05. The coefficient of determination (R²) is 20.8%, indicating that capital structure and liquidity explain 20.8% of profitability variation, while 79.2% is explained by other factors. In conclusion, mining companies should maintain a balanced capital structure and liquidity in order to enhance sustainable profitability